Efektivitas dan Persepsi Pelaksanaan Penyuluhan Pertanian pada Masa Pandemi Covid 19 - Mohamad Ikbal Bahua (Fakultas Pertanian, Universitas Timor, 2021)
This study aims (1) to analyze the effectiveness of the implementation of agricultural extension and (2) to analyze farmers' perceptions of the implementation of the agricultural extension during the Covid 19 pandemic. The research was conducted in North Gorontalo Regency, through a survey method from June to September 2020. The sample of research respondents was 60 corn farmers who were taken by purposive sampling. To determine the effectiveness and perception of the research data, the analysis used semantic differential analysis. The results showed that the implementation of the agricultural extension during the Covid 19 pandemic was